The Impact of ESG on Financial Distress: Moderating Effects of Firm Characteristics in Energy and Manufacturing Firms in ASEAN-5 - Lina Lina; Vonnie Anatha (ccounting Department, Universitas Syiah Kuala, Indonesia, 2026)
This study empirically examines the link between ESG performance and financial distress in energy and manufacturing firms across ASEAN-5. The study employs firm-level panel data (n=550) for 2020–2024 and uses a fixed-effects logistic regression. Results show that stronger ESG engagement reduces the likelihood of financial distress. Firm size strengthens this effect, while firm age has no significant impact. The findings highlight ESG’s role in enhancing financial resilience, especially for larger firms, and guide policymakers and corporate leaders in shaping sustainability and risk management strategies.